Using the Higher Education Performance Framework to Assess Service Quality and Satisfaction among Private University Students - Eric E. Mang’unyi; Krishna K. Govender (International Review of Management and Marketing, 2017)
The theory of higher education performance (HEdPERF) developed by Firdaus (2006), comprising academic, non-academic, reputation, access, programme and health aspects of service quality (SQ), is adapted and used to interpret the customer satisfaction among a stratified sample of students at private universities in Kenya, using a hypothetico-deductive viewpoint. From the data analysed from 522 self-completed surveys, it became apparent from a prediction of the level of SQ delivered, that there were no significant differences across SQ indexes among the students. It is opined that the “HEdPERF” model can enable HE managers to identify aspects by which students gauge the quality of the service. Managers need to pay more attention on managing the students’ overall satisfaction, by bridgeng the “gap” through improved academic and health service provision. Future researchers may also use combined methodological approaches to eliminate the limitations of a single method.